Refractive index and thickness determination in Langmuir monolayers of myelin lipids - Pusterla, Julio Martín (2017)
Langmuir monolayers at the air/water interface are widely used as biomembrane models and for amphiphilic molecules studies in general. Under controlled intermolecular organization (lateral molecular area), surface pressure, surface potential, reflectivity (R) and other magnitudes can be precisely determined on these planar monomolecular films. However, some physical parameters such as the refractive index of the monolayer (n) still remain elusive. The refractive index is very relevant because (in combination with R) it allows for the determination of the thickness of the film. The uncertainties of n determine important errors that propagate non-linearly into the calculation of monolayers thickness. Here we present an analytical method for the determination of n in monolayers based on refractive index matching. By using a Brewster angle microscopy (BAM) setup and monolayers spread over subphases with variable refractive index (n2), a minimum in R is search as a function of n2. In these conditions, n equals n2. The results shown correspond to monolayers of myelin lipids. The n values remain constant at 1.46 upon compression and equals the obtained value for myelin lipid bilayers in suspension. The values for n and R allow for the determination of thickness. We establish comparisons between these thicknesses for the monolayer and those obtained from two X-ray scattering techniques: 1) GIXOS for monolayers at the air/water interface and 2) SAXS for bilayers in bulk suspension. This allows us to conclude that the thickness that we measure by BAM includes the apolar and polar headgroup regions of the monolayer.